The Influence of Gender on Rural Honduran Women’s Participation and Leadership in Community Groups - Jera Niewoehner-Green; Nicole Stedman; Sebastian Galindo; Sandra Russo; Hannah Carter; Kathy Colverson (Journal of International Agricultural and Extension Education, 2019)
Throughout Latin America, increasing women’s leadership has been part of many development efforts. However, extensive research on this topic, especially with rural indigenous women, is limited in the literature. Barriers and opportunities for women to participate in leadership within their communities and local organizations may be related to economic, psychological, and social factors that influence their personal empowerment. This study used mixed methods to explore multiple perspectives of community participation and leadership of two Lenca villages in the western department of Lempira, Honduras. The findings from this study provide insight into structural constraints on women’s leadership in the community, and how gender affects engagement in agriculture. The importance of this research is its applicability to agricultural extension pracitionners working in rural communities where participation in traditional gender roles may create gaps in women’s opportunities to engage in decision-making around agriculture, participate in community development, and be valued as leaders. For communities whose livelihoods rely on agriculture, understanding barriers to women’s participation can aid extension practitioners working to increase food security, as women play key roles in both agriculture and in supporting their families.
Keywords: gender; women; agriculture; leadership; participation